“An Icelandic Driver”: J. Magnús Bjarnason’s Story as a History of Immigrant Hierarchy, Erasure, and Antisemitism in Nineteenth-Century Halifax: A Translation - Lalonde, Jay L. (Scandinavian-Canadian Studies / Études scandinaves au Canada, 2023)
“An Icelandic Driver” is the first English translation of the short story (or novella) “Íslenzkur ökumaður” by the Icelandic-Canadian writer Jóhann Magnús Bjarnason. The story, first published in 1910, offers a unique point of view on turn-of-the-century Halifax, Nova Scotia. While most texts by Icelandic immigrant authors narrowly focus on the experience of their compatriots in isolated rural settlements, this story provides a much richer and more complex portrayal of urban—rather than rural—life. It is inhabited by various immigrants, foreigners, and outsiders, who shape the protagonist’s understanding of his new home. While this portrayal allows for a much more nuanced view, it also reveals a rigid immigrant hierarchy, xenophobia, and antisemitism—all omnipresent and to a large extent internalized by the protagonist.